Light intensity and wavelength influence development, reproduction and locomotor activity in the predatory flower bug Orius sauteri (Poppius) (Hemiptera: Anthocoridae) - Wang, S.; Tan, X. L.; Michaud, J. P.; Zhang, F.; Guo, X. (My University, 2013)
Light wavelength and intensity are physical factors that can affect arthropod development and reproduction. The present study examined the development, reproduction and locomotor activity of the predatory flower bug, Orius sauteri (Poppius) (Hemiptera: Anthocoridae), under five light intensities (1000, 2000, 3000, 4000 and 5000 lux) and five wavelengths [red (678.5 nm), green (620.0 nm), yellow (581.7 nm), blue (478. 1 nm) and white (all wavelengths)] at constant temperature (25 °C) and RH (70%). The duration of nymphal development was extended at lower light intensities, primarily due to effects on the first three instars. Under white, yellow and green light, O. sauteri completed development in 18.0 d, but blue light extended development by 3.2 d and red light extended it by 7.4 d. Although lower light intensities extended the preoviposition period and reduced fecundity, they improved egg fertility. Both red and blue light negatively affected preoviposition period, fecundity and egg fertility. Whereas adult female mean walking speed over a five min period was reduced at lower light intensities, longer wavelengths (yellow and red) increased it, ostensibly reflecting an avoidance response. The respiration quotient of adult O. sauteri females was also elevated under red light conditions. These findings are informative for optimizing O. sauteri mass-rearing procedures and maximizing its efficacy as a biological control agent in greenhouse cultures.
Citation: Wang, S., Tan, X. L., Michaud, J. P., Zhang, F., & Guo, X. (2013). Light intensity and wavelength influence development, reproduction and locomotor activity in the predatory flower bug Orius sauteri (Poppius) (Hemiptera: Anthocoridae). Retrieved from http://krex.ksu.edu
Keywords: Fecundity; Fertility; Locomotion; Mating; Oviposition; Respiration quotient